Medical Check of the Shoulder Girdle of High-School Pitchers in 2002 - Suzuki, Hideki; Aib, Sachiko; Oosawa, Toshihisa; Takagishi, Kenji; Hasegawa, Hitoshi; Kurosawa, Kazuya; Watanabe, Hideomi (Kita Kantō igaku (The Kitakanto Medical Journal), 2004)
Background & Aims : To clarify possible prognostic factors contributing to shoulder girdle disorders. Methods : Subjects were 122 pitchers registered with the Gunma High School Baseball Association who underwent medical check. Results : The range of internal rotation of the shoulder joint was significantly reduced on the pitching side, while that of external rotation was extended. Twenty-eight pitchers (23.0%) reported shoulder pain. Factors significantly related to pain included maximum pitching ball-speed, tenderness at the coracoid process, impingement signs, and superior labrum both anterior and posterior (SLAP) lesion signs, but not shoulder instability. There were no significant radiological alterations related to pain. Conclusions : These results suggest that impingement syndrome and SLAP lesion may play an important role in the induction of shoulder pain, and physical therapy and careful follow-up are needed for high school pitchers with these signs.